A new approach to maternal mortality: the role of HIV in pregnancy - Gorman SE (Dove Medical Press, 2013)
Sara E GormanDepartment of Epidemiology, Harvard University, Boston, MA, USAAbstract: As 2015 quickly approaches, we have been made increasingly aware of our progress toward Millennium Development Goals (MDGs). However, one MDG has been particularly recalcitrant to progress: MDG 5, namely, improving maternal health. Few countries are on track to achieve the first part of MDG 5's goals, reducing maternal mortality by 75%. This article addresses the key priority issues of maternal health as part of sexual and reproductive health issues and maternal health and communicable diseases. It argues that only an integrative approach to the twin challenges of HIV and maternal mortality can help reduce devastatingly high rates of maternal deaths worldwide, especially in sub-Saharan Africa. The article reenvisions the MDGs not as separate, independent tasks, but as related, cohesive issues for which a holistic approach is needed. New causes of the relationship between HIV and maternal mortality are considered, and possible solutions are broached.Keywords: HIV, maternal mortality, Millennium Development Goals, integrated approach to maternal health